2006
DOI: 10.1111/j.1526-4637.2006.00146.x
|View full text |Cite
|
Sign up to set email alerts
|

Pain among Veterans of Operations Enduring Freedom and Iraqi Freedom: Table 1

Abstract: The results of this preliminary study suggest that a substantial percentage of OEF/OIF veterans will experience clinically significant pain following their military service.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
58
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 208 publications
(62 citation statements)
references
References 14 publications
4
58
0
Order By: Relevance
“…The finding regarding pain is of particular concern since studies of OIF/OEF Veterans have found prevalence rates for chronic widespread pain ranging from 29 to 47 percent [14,30]. Pain is often comorbid with mental health conditions such as PTSD and depression (e.g., [31,32]); thus, it is not surprising that individuals who are limited by their mental health conditions may also report high levels of pain.…”
Section: Discussionmentioning
confidence: 93%
“…The finding regarding pain is of particular concern since studies of OIF/OEF Veterans have found prevalence rates for chronic widespread pain ranging from 29 to 47 percent [14,30]. Pain is often comorbid with mental health conditions such as PTSD and depression (e.g., [31,32]); thus, it is not surprising that individuals who are limited by their mental health conditions may also report high levels of pain.…”
Section: Discussionmentioning
confidence: 93%
“…Recently returned Operation Iraqi Freedom (OIF) and Operation Enduring Freedom (OEF) veterans represent a unique population served by the VA. Having recently been engaged in a physically demanding environment, these veterans, many with physical and/or mental sequelae from their tour of duty, face an abrupt transition to civilian life [11,[21][22][23][24][25][26][27][28]. In light of the growing body of evidence demonstrating the benefits of physical activity, including decreasing both obesity-associated morbidity and mortality [29][30] and disability from chronic musculoskeletal pain [31], OIF/OEF veterans using the VA are an ideal population for interventions centered around increasing physical activity.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also reported that a substantial percentage of OIF/OEF and Persian Gulf war veterans experience chronic pain following their period of Active Duty [8][9][10]. Mounting evidence exists within the scientific literature regarding the co-occurrence of and the relationship between PTSD and chronic pain [11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%